Sleep and affect : assessment, theory, and clinical implications - Babson, Kimberly A. (Kimberly Anne), 1983-; Feldner, Matthew T. (London : Academic Press, 2015)
Sleep and Affect: Assessment, Theory, and Clinical Implications synthesizes affective neuroscience research as it relates to sleep psychology and medicine. Evidence is provided that normal sleep plays an emotional regulatory role in healthy humans. The book investigates interactions of sleep with both negative and positive emotions, along with their clinical implications. Sleep research is discussed from a neurobiological, cognitive, and behavioral approach. Sleep and emotions are explored across the spectrum of mental health from normal mood and sleep to the pathological extremes. The book, additionally, offers researchers a guide to methods and research design for studying sleep and affect. This book will be of use to sleep researchers, affective neuroscientists, and clinical psychologists in order to better understand the impact of emotion on sleep as well as the effect of sleep on physical and mental well-being. Contains neurobiological, cognitive, and behavioral approaches Explains methods for examining sleep and affect Summarizes research on sleep and specific affect states Translates research for clinical use in treating disorders.
Part 1. Definitions. -- 1. Neurophysiology of sleep and circadian rhythms / Jeff Dyche, Katherine C. Couturier, M. Kate Hall -- 2. Human emotions : a conceptual overview / Andreas Keil, Vladimir Miskovic -- 3. Sleep, emotions, and emotion regulation : an overview / Christopher P. Fairholme, Rachel Manber -- Part 2. Methods. -- 4. Methodology for the assessment of sleep / Christopher B. Miller, Simon D. Kyle, Kerri L. Melehan, Delwyn J. Bartlett -- 5. The elicitation and assessment of emotional responding / Sarah J. Bujarski, Emily Mischel, Courtney Dutton, J. Scott Steele, Joshua Cisler -- 6. Methodological considerations when integrating experimental manipulations of sleep and emotion / Jared Minkel, Samantha Phillips -- Part 3 : Evidence regarding sleep and specific types of affect. -- Section 1. Sleep and negative affect. -- 7. The interrelations between sleep and fear/anxiety : implications for behavioral treatment / Kimberly A. Babson -- 8. Nightmares and the mood regulatory functions of sleep / Patrick J. McNamara, Umberto Prunotto, Sanford H. Auerbach, Alina A. Gusev -- 9. Isolated sleep paralysis and affect / Brian A. Sharpless -- 10. Sleep and repetitive thought : the role of rumination and worry in sleep disturbance / Vivek Pillai, Christopher L. Drake -- 11. Sleep, sadness, and depression / Rachel Manber, Christopher P. Fairholme -- 12. The interrelations between sleep, anger, and loss of aggression control / Jeanine Kamphuis, Marike Lancel -- Section 2. Sleep and positive affect. -- 13. Positive affect as resilience and vulnerability in sleep / Anthony D. Ong, Emily D. Bastarache, Andrew Steptoe -- 14. Sleep and biological rhythms in mania / Rebecca Robillard, Ian B. Hickie -- 15. Physical activity, sleep, and biobehavioral synergies for health / Matthew P. Buman, Shawn D Youngstedt -- 16. Mindfulness, affect, and sleep : current perspectives and future directions / Sheila N. Garland, Willoughby Britton, Noemi Agagianian, Roberta E. Goldman, Linda E. Carlson, Jason C. Ong -- Section 3. Evidence regarding sleep and affect among special populations. -- 17. Pain and sleep / Timothy Roehrs, Thomas Roth -- 18. The impact of sleep on emotion in typically developing children / Reut Gruber, Soukaina Paquin, Jamie Cassoff, Merrill S. Wise -- 19. Sleep and adolescents / Eleanor L. McGlinchey -- 20. The relationship between sleep and emotion among the elderly / Pascal Hot, Isabella Zsoldos, Julie Carrier -- Part 4. Future directions. -- 21. Sleep and affect : an integrative synthesis and future directions / Kimberly A. Babson, Matthew T. Feldner.
Includes bibliographical references and index.
Print version record.
Keywords: Sleep -- Psychological aspects; Affect (Psychology); Sleep disorders; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Affect (Psychology); Sleep disorders; Sleep -- Psychological aspects; Sleep; Electronic books